2017
DOI: 10.1002/pssr.201700178
|View full text |Cite
|
Sign up to set email alerts
|

UV radiation hardness of photovoltaic modules featuring crystalline Si solar cells with AlOx/p+‐type Si and SiNy/n+‐type Si interfaces

Abstract: We report on the UV radiation hardness of photovoltaic modules with bifacial n-type Passivated Emitter and Rear Totally diffused crystalline Si cells that are embedded in an encapsulation polymer with enhanced UV transparency. Modules with front junction cells featuring an AlO x /p þ -type Si passivation interface at the illuminated side are stable for a UV irradiation dose of 598 kWh m À2 . In contrast, irradiating modules with back junction cells featuring an a-SiN y /n þ -type Si passivation interface at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Please note that we demonstrated that this surface is UV stable in the laboratory thanks to the Al 2 O 3 /SiN x passivation stack. [ 32 ] We, therefore, consider POLO BJ cells are suitable for modules with UV transparent encapsulation polymers for achieving higher module power output and efficiencies. [ 33 ] We thus conclude that POLO BJ cells are a quite promising option for implementing electron‐collecting passivating contacts into p‐type industrial silicon solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Please note that we demonstrated that this surface is UV stable in the laboratory thanks to the Al 2 O 3 /SiN x passivation stack. [ 32 ] We, therefore, consider POLO BJ cells are suitable for modules with UV transparent encapsulation polymers for achieving higher module power output and efficiencies. [ 33 ] We thus conclude that POLO BJ cells are a quite promising option for implementing electron‐collecting passivating contacts into p‐type industrial silicon solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, UV exposure can disrupt this surface passivation by damaging the passivation layer itself or the passivation layer/Si cell interface 11–14 as well as causing subsurface damage in the silicon 15,16 . Different research groups have identified distinct wavelengths in the 300–400 nm spectral range as the damaging wavelengths of incident radiation for UV degradation of Si solar cells 13,14,17–24 …”
Section: Introductionmentioning
confidence: 99%
“…For example, JinkoSolar published an efficiency loss of −4% to −7% in industrial solar cells after exposure to approximately 540 MJ·m −2 (150 kWh·m −2 , i.e., 25 sunny days AM1.5G) of UVA light 25 . In some PERT cells, a UV dose of 1.8 GJ·m −2 at 40°C resulted in 15% power loss 21 . We note that the UVID described here results from the surface region and/or interface effect(s)—distinct from the typical LID (a fast initial power decrease attributed to the evolution of boron‐oxygen and boron‐iron complexes in the bulk of silicon) 26,27 and light and elevated temperature induced degradation (“LETID,” a slow progressing degradation activated during light exposure or via electrical current at temperatures above 60°C) 28,29 …”
Section: Introductionmentioning
confidence: 99%
“…3 to show that DS layers on high efficient c-Si and mc-Si solar modules can be detrimental for enhancing the efficiency of such devices, as we have explained elsewhere [25]. However, the high UV transparency of such devices could accelerate the passivation degradation of the solar cell, as it has been described in recent works [43,44]. Then, the DS can be also useful for absorbing UV radiation and, therefore, to slow the passivation degradation reported.…”
Section: -Results and Discussionmentioning
confidence: 76%